2023
DOI: 10.1136/bmjopen-2023-075290
|View full text |Cite
|
Sign up to set email alerts
|

Use of social media in recruiting young people to mental health research: a scoping review

Megan V A Smith,
Dominique Grohmann,
Daksha Trivedi

Abstract: ObjectivesThis review explored the literature on the use of social media in recruiting young people, aged 13–18 years, to mental health research. It aimed to identify barriers and facilitators to recruitment and strategies to improve participation in future research.DesignScoping review.Data sourcesArticles published between January 2011 and February 2023 were searched for on PubMed, Scopus, Medline (via EBSCOhost) and Cochrane Library databases.Eligibility criteriaStudies that outlined social media as a recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Previous studies on the feasibility of different recruitment approaches have reported recruitment rates, that is, the ability to recruit a certain number of eligible individuals over a specified timeframe, as a way to evaluate the practicality and feasibility of different methods of outreach (Bowen et al, 2009;Brøgger-Mikkelsen et al, 2020;Orsmond & Cohn, 2015). To evaluate our recruitment approach, feasibility in the current study was defined as our team's ability to connect with 150 teens who met inclusion criteria for our digital intervention study using our two online recruitment methods over 6 months, a timeframe comparable to other digital intervention studies among teens (Ali et al, 2022;Salem et al, 2023;Smith et al, 2023). Both recruitment approaches were used for approximately 6 months in total.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on the feasibility of different recruitment approaches have reported recruitment rates, that is, the ability to recruit a certain number of eligible individuals over a specified timeframe, as a way to evaluate the practicality and feasibility of different methods of outreach (Bowen et al, 2009;Brøgger-Mikkelsen et al, 2020;Orsmond & Cohn, 2015). To evaluate our recruitment approach, feasibility in the current study was defined as our team's ability to connect with 150 teens who met inclusion criteria for our digital intervention study using our two online recruitment methods over 6 months, a timeframe comparable to other digital intervention studies among teens (Ali et al, 2022;Salem et al, 2023;Smith et al, 2023). Both recruitment approaches were used for approximately 6 months in total.…”
Section: Methodsmentioning
confidence: 99%